Novel Insights Into the Mechanisms of Abdominal Pain in Obstructive Bowel Disorders - Shi, Xuan-Zheng; Lin, You-Min; Hegde, Shrilakshmi (Frontiers in Integrative Neuroscience, 2018)
Obstructive bowel disorders (OBD) are characterized by lumen distention due to mechanical or functional obstruction in the gut. Abdominal pain is one of the main symptoms in OBD. In this article, we aim to critically review the potential mechanisms for acute and chronic pain in bowel obstruction (BO). While clustered contractions and associated increase of intraluminal pressure may account for colicky pain in simple obstruction, ischemia may be involved in acute pain in severe conditions such as closed loop obstruction. Recent preclinical studies discovered that visceral sensitivity is increased in BO, and visceral hypersensitivity may underlie the mechanisms of chronic abdominal pain in BO. Mounting evidence suggests that lumen distension, as a circumferential mechanical stretch, alters gene expression (mechano-transcription) in the distended bowel, and mechano-transcription of nociceptive and inflammatory mediators plays a critical role in the development of visceral hypersensitivity in BO. Mechano-transcription of nerve growth factor (NGF) in gut smooth muscle cells is found to increase voltage-gated Na+ channel (Nav) activity of the primary sensory neurons by up-regulating expression of TTX-resistant Nav1.8, whereas mechanical stretch-induced brain-derived neurotrophic factor (BDNF) reduces Kv currents especially A-type (IA) currents by down-regulating expression of specific IA subtypes such as Kv1.4. The NGF and BDNF mediated changes in gene expression and channel functions in the primary sensory neurons may constitute the main mechanisms of visceral hypersensitivity in OBD. In addition, mechanical stretch-induced COX-2 and other inflammatory mediators in the gut may also contribute to abdominal pain by activating and sensitizing nociceptors.